Next-generation sequencing for pediatric CNS tumors: does it add value in a middle-income country setup? - Amayiri, Nisreen; Al-Hussaini, Maysa; Maraqa, Bayan; Alyazjeen, Shaza; Alzoubi, Qasem; Musharbash, Awni; Ibrahimi, Ahmad Kh.; Sarhan, Nasim; Obeidat, Mouness; Hawkins, Cynthia; Bouffet, Eric (Frontiers in Oncology, 2024)
Introduction: Advances in molecular diagnostics led to improved targeted interventions in the treatment of pediatric CNS tumors. However, the capacity to test for these is limited in LMICs, and thus their value needs exploration. Methods: We reviewed our experience with NGS testing (TruSight RNA Pan-Cancer-seq panel) for pediatric CNS tumors at KHCC/Jordan (March/2022- April/2023). Paraffin blocks’ scrolls were shipped to Sickkids laboratory based on the multidisciplinary clinic (MDC) recommendations. We reviewed the patients’ characteristics, tumor types and the NGS results’ impact on treatment Results: Of 237patients discussed during the MDC meetings, 32 patients (14%) were included. They were 16 boys and 16 girls; median age at time of testing was 9.5 years (range, 0.9- 21.9years). Twenty-one samples were sent at diagnosis and eleven upon tumor progression. The main diagnoses were low-grade-glioma (15), high-grade-glioma (10), and other histologies (7). Reasons to request NGS included searching for a targetable alteration (20), and to better characterize the tumor behavior (12). The median turnaround time from samples’ shipment to receiving the results was 23.5 days (range, 15-49days) with a median laboratory processing time of 16 days (range, 8-39 days) at a cost of US$1,000/sample. Nineteen (59%) tumors had targetable alterations (FGFR/MAPK pathway inhibitors (14), check-point inhibitors (2), NTRK inhibitors (2), and one with PI3K inhibitor or IDH1 inhibitor. Two rare BRAF mutations were identified (BRAFp.G469A, BRAFp.K601E). One tumor diagnosed initially as undifferentiated round cell sarcoma harbored NAB2::STAT6 fusion and was re-classified as an aggressive metastatic solitary fibrous tumor. Another tumor initially diagnosed as grade 2 astroblastoma grade 2 was re-classified as low-grade-glioma in the absence of MN1 alteration. NGS failed to help characterize a tumor that was diagnosed histologically as small round blue cell tumor. Nine patients received targeted therapy; dabrafenib/trametinib (6), pembrolizumab (2), entrectinib (1); mostly upon tumor progression (7). Conclusions: In this highly selective cohort, a high percentage of targetable mutations was identified facilitating using targeted therapies. Outsourcing of NGS testing was feasible, however, criteria for case-selection are needed. In addition, local capacity-building in conducting the test, interpretation of the results and access to “new-drugs” continues to be a challenge in LMICs